Gender Difference in the Relationship of Physical Activity and Subjective Happiness Among Chinese University Students - Jiang, Wenning; Luo, Jin; Guan, Hannan (Frontiers in Psychology, 2021)
Background: Gender makes a difference in health and physical activity (PA). This research aimed to identify the gender difference in the relationship of PA and subjective happiness among Chinese university students. Methods: A cross-sectional survey was conducted in Shanghai Jiao Tong University from July 7 to 17 in 2021, using an anonymous online self-report questionnaire. The questionnaire included the Chinese version of the International Physical Activity Questionnaire-Short Form (IPAQ-SF), the Subjective Happiness Scale (SHS), the Depression Anxiety Stress Scale-21(DASS-21). The demographic and health-related factors were also reported. Linear regression was carried out to identify the relationship of PA and subjective happiness. Findings: In total, 1,512 students (1,108 males and 404 females) from three comprehensive schools completed the survey. The SHS score was 17.20 ± 3.44, and it was 17.00 ± 3.23 in males, and 17.75 ± 3.93 in females, respectively (p < 0.001). There was no gender difference in vigorous, moderate PA, or walk min/week, while female students had longer sedentary behavior hours/day than males. Male students scored higher in each subscale of DASS-21. After controlling for confounders, vigorous PA min/week (β = 0.002, p = 0.002) and sedentary behavior hours/day (β = 0.168, p = 0.005) were significantly positively associated with happiness in male students. In contrast, walk min/week (2= 0.002, p = 0.005) was significantly positively associated with happiness in female students. Interpretation: This research demonstrated a significant gender difference in the association between PA and happiness. Policymakers and college management should pay more attention to PA programs to promote students’ happiness and mental health status.